Molecular and biochemical characterization of phosphate-solubilizing Pseudomonas sp. isolated from oil palm soil - Kooshan, Moloud (2015)
Phosphorous (P) is one of the most essential macronutrients required for plant growth and development. The objectives of the present study were to select Pseudomonas from soils of oil palm capable of solubilizing phosphate under tropical environment by various biochemical and genotypical method have been used. The study carried out to determine the population distribution of phosphate solubilizing Pseudomonas in oil palm soil by Standard Plate Count. The results showed that the distribution of phosphate solubilizing bacteria and phosphate solubilizing Pseudomonas population in UPM were higher than the rest. Twenty five isolates were able to grow and form clearing zone in NBRIP (National Botanical Research Institute’s Phosphate) medium, PVK (Pikovskayas) and other different carbon and nitrogen sources. The best isolates were 43Dengkil, 9Dengkil, 10Dengkil and 15Dengkil which solubilized phosphate on NBRIP better than other isolates. Meanwhile, the best isolate on PVK was 15Dengkil. The result of culturing the isolates in NBRIP indicated that among all carbon sources glucose was the best carbon sources for phosphate solubilization and KNO3 was less effective compared to (NH4)NO3 when it was used as a source of nitrogen. All the isolates were acid producers and among them, 633UPM and 144UPM, after 5 days of culture, 555UPM and 23Dengkil after 8 days of culture respectively, showed the lowest pH. The effective phosphate solubilizer isolates after 5 days were 48Semenyih and 45Dengkil, 5Semenyih, and after 8 days were 45Dengkil, 5Semenyih, followed by 48Semenyih respectively. Initial confirmation of their genus level identity as Pseudomonas was arrived by amplification of 16S rDNA sequence. The result of a BLAST search of 16S rDNA sequences of Pseudomonas compared with the available 16S rDNA sequences in the GenBnak database indicated that all of the Pseudomonas isolates belonged to gamma proteobacteria subdivision. Isolates 59Semenyih, 62Dengkil, 555UPM, 43Dengkil, 69Semenyih and 103Semenyih had more than 80% similarity to Pseudomonas species. The diversity among isolates was determined by REP-PCR (Repetitive Extragentic Palindromic Elements). Based on REP-PCR pattern isolates were classified into seven groups (A, B, C, D, E, F, and G). The cluster showed that in group A, isolates 9Dengkil, 10Dengkil, 15Dengkil, 23Dengkil and 45Dengkil were totally similar to each other. Cluster B included 43Dengkil, 62Dengkil isolates. Clusters C and D included isolates 103UPM and 59Semenyih respectively. Four isolates fell into cluster E and these isolates were totally similar to each other. Cluster F contained isolates 144UPM and 625UPM. Cluster G consisted of 4 isolates and also cluster H included 5 isolates. Also, this study concluded that the cluster analysis of Pseudomonas based on REP-PCR identified clusters A, B, C, D, E and F approximately with genetic distance=0.34. The results presented here clearly establish that REP sequences (elements) are present in genome of phosphate solubilizing Pseudomonas isolated from oil palm soils.